Evaluation of Quality and Availability of Arabic Web-Based Information on Dry Socket - Saeidi, Abdullah Abdulaziz; Shahadah, Samer; Alharbi, Abdulaziz; Alturkistani, Abdulrahman; Gamar Elanbya, May; Alassaf, Muath; Elsayed, Shadia (European Journal of General Dentistry, 2025)
This study aimed to assess the quality and availability of Arabic-language internet-based information on alveolar osteitis or dry socket.The present cross-sectional study included the first 50 websites that appeared through Bing, Google, and Yahoo search engines for the terms alveolar osteitis or dry socket or alveolitis to evaluate the content, quality, and readability of the available Arabic information. The Journal of the American Medical Association (JAMA) criteria for website analysis, the Health on the Net (HON), and the DISCERN instrument were used to evaluate the quality of the online material. Three metrics were used to evaluate the readability: Simplified Measure of Gobbledygook (SMOG), the Flesch–Kincaid Grade Level (FKGL), and the Flesch Reading Ease (FRES) scores.Based on affiliation, dental/medical centers have the highest representation, followed by nonprofit organizations. Visuals like images are moderately used. The reliability DISCREN domain scores indicated generally poor balance in the materials, though relevance is a notable strength. Overall rating (Q16) revealed that the materials are rated as moderately useful overall with relatively low variability (mean: 2.93; standard deviation [SD]: 0.776). Governmental/university websites excel in meeting the JAMA benchmarks. Dental/medical centers and nonprofit organizations showed better overall JAMA performance than commercial websites. According to the FRES scale, the majority of websites are written in a simple, accessible manner, suitable for general users. Most websites offer moderate-quality information (mean = 38.19; SD = 9.035 [range: 22–56]).Most websites had medium-quality data on dry socket without achieving high reliability or usability or treatment risk by the majority of websites with nonprofits websites leading in this regard, followed by dental/medical centers.
Keywords: dry socket; alveolitis; postextraction; complications; osteitis